Private Islamic primary school teachers' commitment in human capital development in Malaysia - Suhid, Asmawati; Mohd Fakharuddin, Fathiyah; Roslan, Samsilah; Abdul Mutalib, Lukman; Che Noh, Mohd Aderi (Mediterranean Center of Social and Educational Research, 2014)
In general, education is a continuous process to educate and develop individuals to a more meaningful life in this world and in the hereafter. In order to educate, the role of education is to nuture and develop human interests, the importance of which had been acknowledged by most societies. Thus various measures and efforts have been made to strengthen the educational process to be followed by each generation level. Currently, PIPS is an alternative education for parents in Malaysia other than the National Schools under the Ministry of Education. The mushrooming of the Private Islamic Primary Schools has been seen as a result of the high demand from the society. The society, particularly the parents have put high expectations in the education in these schools which emphasized not only the religious subjects but also the academic ones to produce a balanced and integrated human capital. Thus, this study was carried out to explore the PIPS teachers’ commitment in fulfilling the responsibilities and trusts undertaken to realise the noble needs.